Cultural nuances of thwarted belongingness and perceived burdensomeness linked to Asian American suicidality - Lee, Hye Jin (Kansas State University, 2024)
Asian Americans and Pacific Islanders (AAs) represent one of the fastest-growing ethnic groups in the United States, with an 88% increase from 2000 to 2019. The rate of suicide among AAs has also risen alongside this population growth. Unique cultural factors distinguish AA experiences from those of the dominant American culture, such as cultural identity, conflict due to parental expectations, depression, and discrimination. This study aims to broaden the understanding of suicidality among 195 second-generation AAs by examining how distinctive AA cultural factors are captured by the Interpersonal Theory of Suicide (ITS). The path analysis results found belongingness and burdensomeness, two main concepts from ITS, mediated cultural factors and suicidality. First, increased integration within both the Asian and American cultures increased belongingness, which in turn reduced suicidal ideation. Next, conflict due to parental expectation and depression increased burdensomeness which, in turn, increased suicidal ideation, plan and attempt. Last, although discrimination was linked to thwarted belongingness and suicidality, thwarted belongingness did not mediate the relationship between discrimination and suicidality. The clinical and research implications of the findings are discussed.
Keywords: Bicultural identity integration; Suicidal ideation; Discrimination; Parental expectations; Depression